2015
DOI: 10.1162/jocn_a_00752
|View full text |Cite
|
Sign up to set email alerts
|

The Attentional Blink Impairs Detection and Delays Encoding of Visual Information: Evidence from Human Electrophysiology

Abstract: Abstract■ This article explores the time course of the functional interplay between detection and encoding stages of information processing in the brain and the role they play in conscious visual perception. We employed a multitarget rapid serial visual presentation (RSVP) approach and examined the electrophysiological P3 component elicited by a target terminating an RSVP sequence. Target-locked P3 activity was detected both at frontal and parietal recording sites and an independent component analysis confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 110 publications
(127 reference statements)
8
50
0
Order By: Relevance
“…Lag effects, though of different magnitude, were detected both when the mask was present, t(33) = 10.99, MSE = 0.024, p < 0.0001, and when the mask was absent, t(33) = 3.01, MSE = 0.010, p = 0.005. Results indicated that, in the absence of a mask, an AB effect was only found for T1-present trials, converging with prior studies (Dell'Acqua et al, 2015;Giesbrecht & Di Lollo, 1998;Jannati, Spalek, & Di Lollo, 2010, 2012Sessa et al, 2007). As expected, in mask-present trials the AB deficit (lower accuracy for lag 3 trials vs. lag 8) was more pronounced when more targets were presented (T1-present vs. T1-absent) t(33) = 7.37, MSE = 0.0193, p < 0.001.…”
Section: Behavioralsupporting
confidence: 87%
See 2 more Smart Citations
“…Lag effects, though of different magnitude, were detected both when the mask was present, t(33) = 10.99, MSE = 0.024, p < 0.0001, and when the mask was absent, t(33) = 3.01, MSE = 0.010, p = 0.005. Results indicated that, in the absence of a mask, an AB effect was only found for T1-present trials, converging with prior studies (Dell'Acqua et al, 2015;Giesbrecht & Di Lollo, 1998;Jannati, Spalek, & Di Lollo, 2010, 2012Sessa et al, 2007). As expected, in mask-present trials the AB deficit (lower accuracy for lag 3 trials vs. lag 8) was more pronounced when more targets were presented (T1-present vs. T1-absent) t(33) = 7.37, MSE = 0.0193, p < 0.001.…”
Section: Behavioralsupporting
confidence: 87%
“…The electrophysiological measures showed a smaller P3b amplitude for short lag trials as was previously reported in other studies (Dell'Acqua et al, 2015;Vogel & Luck, 2002;Vogel et al, 1998). This component was however not completely suppressed when the mask was present as was reported by Vogel and Luck (2002).…”
Section: Consciousness and Cognition XXX (Xxxx) Xxx-xxxsupporting
confidence: 86%
See 1 more Smart Citation
“…It has been observed to be modulated by a centrally presented spatial cue in anticipation of an upcoming target, although it is not commonly associated with attentional processing per se, since it is not sensitive to task demands (Hopf & Mangun, 2000). It is considered a measure (amongst others such as P3 and SPCN; see Eimer & Kiss, 2010;Dell'Acqua et al, 2015) involved in the control of attentional resources, therefore playing an important role in the conscious representation during processing of stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…This may be associated with a prefrontal attentional control (i.e., ADAN) to reorient attention towards the extra stimuli. For instance, Dell'Acqua et al (2015), discuss several frontal components thought to reflect attentional control and found that reduced activity in the frontal areas as reflected by the P3a was associated with a delay in the processing of stimuli in the posterior regions (P3b), suggesting that frontal attentional control may be required to establish a different "mental set" in order to allocate resources for the processing and maintenance in VWM of an unexpected (but relevant) stimulus (see for instance Prada, Barceló, Herrmann, & Escera, 2014). As a result, individuals with a greater frontal control in the deployment of attentional resources (i.e., Non-IB), may be able to allow attention-driven gating of relevant visual information (including unexpected stimuli) in the low-level visual processors (e.g., N2pc).…”
Section: Introductionmentioning
confidence: 99%